2021
DOI: 10.1038/s41598-021-95879-7
|View full text |Cite
|
Sign up to set email alerts
|

Combined toxic effects of aflatoxin B2 and the protective role of resveratrol in Swiss albino mice

Abstract: In this study, the toxic effects of aflatoxin B2 (AFB2) on Swiss albino mice and the protective effects of resveratrol were investigated. Physiological (body weight, liver and kidney weight), biochemical (aspartate aminotransferase-AST, alanine transaminase-ALT, blood urea nitrogen-BUN, creatinine, malondialdehyde-MDA and glutathione-GSH) and cytogenetic parameters (micronucleus-MN in buccal epithelium, erythrocyte and leukocyte cells and chromosomal aberrations-CAs) were used to determine the toxic effects. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…The absorbance of the solution was determined spectrophotometrically at 510 nm after 15 min incubation. Quercetin was used as the standard and flavonoid amounts were expressed as mg QE/100 mg dry weight 12 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorbance of the solution was determined spectrophotometrically at 510 nm after 15 min incubation. Quercetin was used as the standard and flavonoid amounts were expressed as mg QE/100 mg dry weight 12 .…”
Section: Methodsmentioning
confidence: 99%
“…The radical scavenging effect of A. lividus extract was tested against superoxide and 2,2-diphenyl-1-picrylhydrazy (DPPH) radicals. Superoxide radical scavenging activity and DPPH removal activity was carried out according to the method suggested by Gündüz et al 12 . BHT was used as a standard in both radical scavenging activities.…”
Section: Methodsmentioning
confidence: 99%
“…The supplementation of 1% Res significantly increased the contents of T-AOC, CAT and SOD in the plasma of broilers [ 26 ]. Studies have shown that Res can protect mice from AFB2 injury, mainly in relation to the scavenging activity of superoxide, H 2 O 2 and 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radicals, and the antioxidant effect [ 33 ]. Our findings demonstrated that AFB1 led to significant oxidative damage and Res reversed the trend, as shown with the decrease in GSH, GSH-ST, T-AOC, CAT and SOD levels decrease and the increase in H 2 O 2 and MDA levels.…”
Section: Discussionmentioning
confidence: 99%
“…NO: B549-150) and creatinine (CAT. NO: C513-480) levels were measured with the help of Medispec 99 M autoanalyzer using commercially available kits (Teco Diagnostics, USA) 10 , 11 .…”
Section: Methodsmentioning
confidence: 99%